Possible involvement of microglial P2RY12 and peripheral IL-10 in postpartum depression - Kim, Hui-Ju; You, Min-Jung; Sung, Soyoung; Rim, Chan; Kwon, Min-Soo (Frontiers in Cellular Neuroscience, 2023)
Postpartum depression (PPD) is another type of depression, including emotional fluctuation, fatigue, and anxiety. Based on the specific event like giving birth, it can be speculated that PPD might have its specific mechanism. Here, we confirmed that dexamethasone (DEX) administration during pregnancy (gestational days 16–18) induced depressive- and anxiety-like behaviors in dam (DEX-dam) after weaning period (3 weeks). DEX-dam showed anxiety-like behaviors in open-field test (OFT) and light–dark test (LD). In addition, DEX-dam exhibited depressive-like behaviors with the increased immobility time in forced swimming test (TST). Molecular analysis confirmed that microglia, rather than neurons, astrocytes, and oligodendrocytes, are involved in anxiety-/depressive-like behaviors. Notably, P2ry12, homeostatic gene, and purinoceptor, along with hyper-ramified form, were reduced in the hippocampus of DEX-dam. In addition, we found that IL-10 mRNA was reduced in lymph nodes without alteration of pro-inflammatory cytokines, such as TNF-α, IL-1β, and IL-6. Interestingly, anxiety-/depressive-like behaviors of DEX-dam were restored with the normalization of P2ry12 and IL-10 after 10 weeks postpartum without antidepressants. Our results propose that stress hormone elevation during pregnancy might be associated with PPD via microglial P2RY12 and peripheral IL-10.